Turkey's Role in Energy Diplomacy from Competition to Cooperation: Theoretical and Factual Projections - Uludag, Mehmet Bulent; Karagul, Soner; Baba, Gurol (International Journal of Energy Economics and Policy, 2013)
This study aims to build up a conceptual framework for energy diplomacy together with examining the development of this concept in world politics. By using these, it attempts to analyse Turkey’s energy diplomacy practice. The study argues that energy diplomacy is an amalgamation of diplomatic methods for utilizing energy (reserves or transfer routes) for maximizing national energy interests in bilateral, multilateral, regional and global relations of energy demand and supply. In this respect, the variables for the formation and the implementation of energy diplomacy are analysed in worldwide historical basis and then with a particular focus on Turkey. Finally, the research focuses on the conditions that Turkey can utilize its energy diplomacy for collaboration, cooperation, and stability rather than struggle, confrontation or conflict. Keywords: Energy diplomacy; energy politics; energy competition JEL Classifications: F53; F55; N40; Q48